Assessing the Impact of Post-Conventional Leaders - Cardillo, Andrea (Journal of Leadership, Accountability and Ethics, 2023)
This article provides a literature review of the state of the art in evaluating the impact of post-conventional stages of development for leaders, focusing on their impact on successful change management, on the integration of environmental concerns and practices, and on stakeholders’ relationships. A synthetic review of the general theory of adult development and of its implications to leadership is provided. Then, the empirical evidence for the impact of post-conventional leaders at work is introduced and discussed. The studies here reviewed suggests that post conventional stages of development can be a strong predictor of leadership performance, in (a) successfully leading organizational change, (b) in driving forward advanced environmentally and socially responsible initiatives, and (c) in creating strong stakeholders’ relationships. Further directions for future research are suggested.